Metoda annuitetowa w zarządzaniu ryzykiem długowieczności w systemach emerytalnych - Szczepański, Marek (Studia Oeconomica Posnaniensia, 2017)
The paper analyses the use of the method of annuity in managing longevity risk in pension systems. The starting point for the discussion was to define longevity risk as well as the classification of different types of products using the financial annuity method. On this basis, the benefits but also the risks associated with the use of annuity products to manage longevity risk in the phase of the payment of benefits from the public (base) and supplementary pension schemes have been evaluated.